Efficacy of Virtual Reality Induced Environmental and Habitual Navigation on Psychological, Cognitive Function that Impacts on Physical Recovery in Patients with Stroke (Indian Journal of Public Health Research & Development, 2021)
[Background] Cognitive dysfunction after a stroke is normal, but it is underdiagnosed and has a badprognosis. In 40-70 percent of stroke survivors, there is a degree of cognitive dysfunction. Similarly,psychometric issues such as anxiety and depression are normal following stroke but are mostly untreated,resulting in a patient’s poor quality of life. Whereas it also has an effect on a person’s rehabilitation. Theuse of traditional methodology has certain beneficial effects, but it is not necessarily handled with theindividual’s own interests in mind. Virtual reality, on the other hand, seems to play a role in dealing withsuch issues, especially where they are linked to neurological disorders. Virtual reality navigation has thepotential to enhance basic cognitive functions such as visuo-spatial perception, executive performance, andattention, both of which can affect one’s psychological state and aid in functional rehabilitation. Cognitivedeficits and social issues must be addressed because they have a detrimental impact on functional abilitiesand quality of life.[Methodology] Twenty-three participants between the ages of 40 and 60 with a stroke diagnosis were chosen.Participants were split into two groups: Group A, which received Virtual Reality induced environmental andhabitual navigation as well as Conventional Physiotherapy, and Group B, which received ConventionalPhysiotherapy as well as cognitive training and relaxation for 4 weeks of duration. The Montreal CognitiveAssessment (MoCA), Hamilton Anxiety Rating Scale (HARS), Hamilton Depression Rating Scale (HDRS),and Functional Independence Measure (FIM) were used to conduct pre and post intervention evaluations.[Conclusion] The study found that combining virtual reality-induced environmental and habitual navigationwith conventional physiotherapy improves cognitive control, psychological function, and functional recoveryin stroke patients more effectively than treating them with conventional physiotherapy alone.
Keywords: Anxiety, Cognitive Impairment, Depression, Environmental Navigation, Functional Recovery, Habitual Navigation, Stroke, Virtual Reality.